TINJAUAN ARTIKEL: PEMASANGAN DENTAL IMPAN SETELAH ELEVASI LANTAI SINUS DENGAN TEKNIK OSTEOTOMI - Halim, Susanna; Muharraran, Firdha; Aulia, Dinda Rizky; Kartika, Disya Citta; Selvina, Weni (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
Dental implant is considered the optimal rehabilitation option for tooth loss, a prevalent issue in Indonesia that can impair oral function. However, it presents technical challenges, particularly in the posterior maxilla where bone volume is limited. This study constitutes a literature review conducted using Google Scholar and Science Direct databases, spanning the years 2000–2024, with the keywords "dental implant", "osteotome technique", "sinus floor elevation", and "case report". The selection process prioritized relevance, scientific rigor, and contribution to the field of study. Two case reports indicate the effectiveness of the osteotome technique in augmenting bone volume and facilitating implant placement in the posterior maxilla. This technique is minimally invasive and expedites the rehabilitation process. Sinus floor elevation using the osteotome technique offers a simpler alternative to conventional procedures, associated with a lower risk of complications. Nevertheless, this technique necessitates operator proficiency and is suitable primarily for cases of mild to moderate bone defects. In conclusion, dental implant placement utilizing the osteotome technique following sinus floor elevation demonstrates efficacy for the rehabilitation of posterior maxillary teeth, contingent upon the consideration of anatomical, aesthetic, economic, and patient preference factors. ABSTRAKKehilangan gigi menjadi masalah umum di Indonesia dan dapat mengganggu fungsi oral. Dental implant merupakan pilihan rehabilitasi terbaik, meskipun memiliki tantangan teknis, khususnya di area posterior maksila dengan volume tulang terbatas. Studi ini merupakan tinjauan literatur menggunakan Google Scholar dan Science Direct pada tahun 2000–2024 dengan kata kunci "dental implant", "osteotome technique", "sinus floor elevation", dan "case report". Seleksi dilakukan berdasarkan relevansi, kualitas ilmiah, dan kontribusi terhadap bidang studi. Dua laporan kasus menunjukkan bahwa teknik osteotomi efektif untuk meningkatkan volume tulang dan memfasilitasi pemasangan implan pada posterior maksila. Teknik ini minimal invasif dan mempercepat proses rehabilitasi. Elevasi sinus dengan osteotomi menjadi alternatif prosedur yang lebih sederhana dibandingkan teknik konvensional, dengan risiko komplikasi yang lebih rendah. Namun, teknik ini memerlukan keterampilan operator dan hanya cocok untuk kasus defek ringan hingga sedang. Dental implant dengan teknik osteotomi setelah elevasi lantai sinus terbukti efektif untuk rehabilitasi gigi posterior maksila, dengan mempertimbangkan faktor anatomi, estetika, ekonomi, dan preferensi pasien.